IMPLEMENTASI KEBIJAKAN BANTUAN STIMULAN PERUMAHAN SWADAYA DI KECAMATAN PARIGI SELATAN - Zulkarnain, Zulkarnain (Katalogis, 2016)
This study aims to find out what caused the implementation of Self-Help Housing Stimulant Assistance Policy in South Parigi District has not been effective. The research type of this study was descriptive qualitative research. The types of data used in this study were primary and secondary data. Those data were collected by means of observations, interviews, documentations, and triangulations. Informant sampling method used in this study was purposive sampling technique. The data analysis used in this study was the Miles and Huberman model, i.e. data reduction, data presentation, and conclusion. The theory used in this study was the theory of van Meter and van Horn, consisting of 6 (six) aspects: the basic measures and policy objectives, policy resources, interagency and inter-implementation communications, characteristics of the implementing agencies, and economic, social, and political conditions, as well as tendencies of the implementers. The results show that the implementation of Self-Help Housing Stimulant Assistance Policy in South Parigi District has not been effective: First, the communication aspect: socializations were done only when the meetings, those were not done on the KPB level resulting public ignorance about the basic measures and policy goals. In addition, the interagency coordination has not been maximal. Second, the characteristics of implementing agencies aspect: the sanctions given by the Department of Public Works and Public Housing of Parigi Moutong Regency on the violating parties were not strict, so as the awareness of the facilitators, the third parties, and the society were not awakened which in turn made the policy implementers not responsible for the policy implementation. Third, the tendencies of the implementers: an attitude that is not considered responsible and transparent, because it provides opportunities for certain parties to collect levies without clear designations and to do dereliction of duty and responsibility so that the distributions of building materials were delayed. Thus, the researcher concludes that policy implementation Self-Help Housing Stimulant Assistance Policy in South Parigi District was not maximal, because only three (3) aspects are met: the basic measures and policy objectives, policy resources, and economic, social, and political conditions. While, other aspects were not maximal: interagency and inter-implementation communications, characteristics of the implementing agencies, and tendencies of the implementers.